2019
DOI: 10.1111/jfpp.14256
|View full text |Cite
|
Sign up to set email alerts
|

Effect of processing on structural, thermal, and physicochemical properties of dietary fiber of culinary banana bracts

Abstract: Dietary fiber (DF) of culinary banana bract was extracted using alkaline extraction (alkaline extracted DF, AEDF) and ultrasound‐assisted extraction in combination with alkaline extraction (ultrasound‐assisted extracted DF, UEDF). The extracted DFs were compared for their composition, structural, thermal, and functional properties. Extraction condition of UEDF was optimized for maximizing the yield through response surface methodology. The maximum yield of DF obtained was 71.05%. Higher total DF (83.38 g/100 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 28 publications
0
27
0
Order By: Relevance
“…Our recent study has shown that the extracted DF (ultrasound‐assisted extracted DF) with higher WHC (water holding capacity), α‐AAIR (α‐amylase retardation index) and GAC (glucose absorption capacity). The smaller particle size and crystalline structure of extracted DF inhibited the contact between α‐amylase and starch and hence, decreased the amount of glucose in serum (Begum & Deka, ). Lower carbohydrate digestibility with lower GI value obtained for pasta and extruded cereal foods with added inulin as a source of soluble DF (Brennan & Samyue, ; Brennan et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…Our recent study has shown that the extracted DF (ultrasound‐assisted extracted DF) with higher WHC (water holding capacity), α‐AAIR (α‐amylase retardation index) and GAC (glucose absorption capacity). The smaller particle size and crystalline structure of extracted DF inhibited the contact between α‐amylase and starch and hence, decreased the amount of glucose in serum (Begum & Deka, ). Lower carbohydrate digestibility with lower GI value obtained for pasta and extruded cereal foods with added inulin as a source of soluble DF (Brennan & Samyue, ; Brennan et al , ).…”
Section: Resultsmentioning
confidence: 99%
“…Similarly , Al-Dhabi et al [3] ) for the extraction of phenolic compounds from Spent coffee ground used Soxhlet extraction system with petroleum ether to defat the samples. Begum and Deka [10] deoiled banana bract using n-hexane, stirring them at 150 rpm for 15 min thereafter centrifuging the sample at 4000 rpm for 20 and finally drying at 50 °C.…”
Section: Pretreatment For Uae Of Bioactive Compoundsmentioning
confidence: 99%
“…UAE of dietary fiber from Citrus Changshan-huyou peels [16] and apple pomace [43] shows better yield, consumed less time and required low temperature as compared to conventional solvent extraction. Similarly, UAE of dietary fiber from culinary banana bract, papaya peel and soyabean residue exhibited higher yield, purity, thermal stability, water-holding, oil-holding and swelling capacities than alkaline extracted dietary fiber [89] , [10] , [78] . UAE dietary fiber contained higher percentages of essential amino acids and essential trace elements while the crystallinity less than alkaline dietary fiber.…”
Section: Application Of Uae In Extraction Of Bioactive Compounds Frommentioning
confidence: 99%
“…The methodology of extraction of DF under optimised condition has been explained in our previous study (Begum et al ., 2019; Begum & Deka, 2019b). The dried culinary banana bract (CBB) was deoiled using n‐hexane.…”
Section: Methodsmentioning
confidence: 99%